The political economy of sugar-sweetened beverage taxation: an analysis from seven countries in sub-Saharan Africa. Issue 1 (1st January 2021) - Thow, Anne Marie; Abdool Karim, Safura; Mukanu, Mulenga M.; Ahaibwe, Gemma; Wanjohi, Milka; Gaogane, Lebogang; Amukugo, Hans Justus; Ruhara, Charles Mulindabigwi; Ngoma, Twalib; Asiki, Gershim; Erzse, Agnes; Hofman, Karen
ABSTRACT: Background : Non-communicable diseases are on the rise across sub-Saharan Africa. The region has become a targeted growth market for sugar-sweetened beverages, which are associated with weight gain, cardiovascular diseases and diabetes. Objective : To identify politico-economic factors relevant to nutrition-related fiscal policies, and to draw lessons regarding strategies to strengthen sugar-sweetened beverages taxation in the region and globally. Methods : We collected documentary data on policy content, stakeholders and corporate political activity from seven countries in east and southern Africa augmented by qualitative interviews in Botswana, Namibia, Kenya and Zambia, and stakeholder consultations in Rwanda, Tanzania and Uganda. Data were analysed using a political economy framework, focusing on ideas, institutions, interests and power, and a 'bricolage' approach was employed to identify strategies for future action. Results : Non-communicable diseases were recognised as a priority in all countries. Kenya, Zambia, Rwanda, Tanzania and Uganda had taxes on non-alcoholic beverages, which varied in rate and tax base, but appeared to be motivated by revenue rather than health concerns. Botswana and Namibia indicated intention to adopt sugar-sweetened beverage taxes. Health-oriented sugar-sweetened beverage taxation faced challenges from entrenched economic policy paradigms for industry-led economic growth and was actively opposed by sugar-sweetened beverage-related industries. Strategies identified to support stronger sugar-sweetened beverage taxation included shifting the economic discourse to strengthen health considerations, developing positive public opinion, forging links with the agriculture sector for shared benefit, and leadership by a central government agency. Conclusions : There are opportunities for more strategic public health engagement with the economic sector to foster strong nutrition-related fiscal policy for non-communicable disease prevention in the region.